Exploring the multifaceted impact of the COVID-19 Pandemic on Teachers' teaching practices - Irene E. Eguico; Maria Nancy Quinco-Cadosales; Daryl F. Quinco; Sharika F. Magcanta; Rosalia E. Celestiano; Rachell-Ann B. Buljatin (Camarines Sur Polytechnic Colleges, 2023)
The devotion and commitment of the teachers allowed for the continuation of instruction during the COVID-19 pandemic. Switching from traditional classroom instruction to an online learning environment was challenging. Learning institutions implemented several teachers' upskilling and skill-building programs to prepare for emergencies. However, teachers were not exempted from the impact of the COVID-19 pandemic. Two hundred eighty-nine (289) teachers from 19 non-sectarian private schools around the Philippines were profiled in the study using quantitative and qualitative research techniques. Roman Catholics and women composed most of the teachers. They employ a range of online technologies and instructional methods. When transitioning to the virtual classroom, teachers faced several difficulties, with intermittent internet connection as the main problem. The teachers agreed that online teaching was advantageous at the onset of the pandemic using varied online tools. They asserted that training initiatives in student motivation and engagement, skill development, and mental health programs are significant to maintaining high-quality teaching and learning.